2021
DOI: 10.1007/s11695-020-05200-0
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of dipeptidyl peptidase 4 activity is associated with weight loss after bariatric surgery

Abstract: Purpose Dipeptidyl peptidase 4 (DPP4) is expressed and secreted by adipocytes. DPP4 induces insulin resistance independently of its effect on glucagon-like peptide 1, thus it is conceivable that DPP4 directly contributes to metabolic dysfunction in patients with morbid obesity. The aim of this study was to investigate the impact of weight loss induced by bariatric surgery on DPP4 activity, and whether these changes are associated with improvements in markers of metabolic dysfunction and fatty liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The concentration of circulating DPP-4 is associated with both visceral adipose tissue volume and adipocyte size, and increases concomitantly with the obesity progression, the development of insulin resistance, and the worsening of glucose metabolic abnormalities ( 26 ). In addition, circulating DPP-4 levels have been shown to increase in patients with non-alcoholic fatty liver disease, and are positively correlated with liver enzymes ( 29 ). Rodent studies indicated that hepatic overexpression of DPP-4 contributes to elevated plasma DPP-4 levels, mediating the crosstalk between liver and adipose tissue by activating macrophages and triggering inflammation ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of circulating DPP-4 is associated with both visceral adipose tissue volume and adipocyte size, and increases concomitantly with the obesity progression, the development of insulin resistance, and the worsening of glucose metabolic abnormalities ( 26 ). In addition, circulating DPP-4 levels have been shown to increase in patients with non-alcoholic fatty liver disease, and are positively correlated with liver enzymes ( 29 ). Rodent studies indicated that hepatic overexpression of DPP-4 contributes to elevated plasma DPP-4 levels, mediating the crosstalk between liver and adipose tissue by activating macrophages and triggering inflammation ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shedding of DPP-4 from the cell surface increases in high glucose conditions ( 32 ), which may contribute to the increased circulating DPP-4 observed in patients with type 2 diabetes. Several treatments for hyperglycemia, including SGLT-2 inhibitors ( 30 ), metformin ( 20 ), calorie restriction ( 33 ), and bariatric surgery ( 29 ), can reduce circulating DPP-4 levels. However, there is relatively little research on the role of circulating DPP-4 activity as an indicator of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…(50) DPP-4 inhibitors typically do not affect weight, while they have been associated with a small amount of weight loss . (51) 4. SGLT2 Inhibitors: A class of medications used to decrease blood sugar called sodium-glucose cotransporter 2 (SGLT2) inhibitors prevent the reabsorption of glucose by the kidneys (52) The renal tubules reabsorb all filtered glucose, and SGLT2 is responsible for more than 90% of this process.…”
Section: Managing Type 2 Diabetes and Its Possible Connection With Ob...mentioning
confidence: 99%
“…Importantly, this only occurs with supraphysiological GLP‐1 concentrations that are 4–5 times higher than those reported after meals. Such elevated levels can be reached in animals that have undergone bariatric surgery (Peterli et al, 2012), as a result of the increased unabsorbed nutrients reaching the distal L‐cells (Larraufie et al, 2019) and/or reduced dipeptidyl peptidase 4 expression (Herz et al, 2021).…”
Section: Vagal‐dependent Actions Of Glp‐1 In the Peripherymentioning
confidence: 99%